“Vês? nós já cantávamos antes!” A fotografia enquanto dispositivo de restauração da música - Castro, Isabel (2019)
During PhD fieldwork within the Goan comunity in Catembe (Mozambique), photography has proved to be significant in mediating my relationship with the participants and understanding issues outside oral discourse. Through photography my colleagues described musical practices, festivals and rituals in which they had participated. Thus, through personal memories suggested by the image, photography prepared the narrative from which the music was materialized. As a document of ethnographic registration, photography has been widely discussed in the context of anthropology. Malinowski (1961) and Lévi-Strauss (2004) opened a pathway both to incorporate photography in anthropology and to analyse and complement ethnographic narratives. Ana Caetano (2007; 2008a; 2008b) refers to photography as an instrument with emotional value, able to create memories of something considered significant, a personal or collective identity branding. However, the relationship between photography and music is under-explored, perhaps due to the apparent contradiction between our relationship with time: music happens in time while the photograph freezes time. Considering my observation of the Goan in Catembe, this article aims to show how photography can help map and reconstruct musical performances reversing apparently static snapshots of time.